Triiodothyronine levels and mortality in children with sepsis and septic shock - Cynthea Prima Destariani; Munar Lubis; Melda Deliana; Gema Nazri Yanni (Paediatrica Indonesiana, 2018)
Background Sepsis is the most common cause of death in infants and children. It can cause hormonal imbalances, such as euthyroid sick syndrome (ESS), which may increase the risk of death. Objective To evaluate a possible correlation between the level of triiodothyronine (T3) and mortality in children with sepsis and septic shock. Methods An observational cohort study was conducted on 80 children with sepsis and septic shock from October 2015 until January 2016Â in Haji Adam Malik General Hospital, Medan. Subjects underwent PELOD score and T3 examinationÂ on the first day admitted in Haji Adam Malik General Hospital. Chi-square test was used to analyze for a correlation between the T3 values and mortality.Â Results Of the 80 consecutive subjects, 39 (48.75%) had low T3 level on the first day. Of these 39 children, 36 (92.3%) died. Subjects with low T3 level had a 6.31 times higher risk of mortality(PR 6.31; 95%CI 2.99 to 13.28; P<0.001). Of the 31 subjects with high PELOD score, 23 (74.2%) had decreased T3 (PR=2.27; 95%CI 1.45 to 3.57; P<0.001). Conclusion Low T3 level has significant relationship with mortality in children with sepsis and septic shock.